An oblique-matrix technique for data integrity assurance - Ghaeb, Jasin Abdullah; Chebil, Jalel (Elsevier, 2009)
Data integrity is insuring that the data retrieved is the same as the data stored or transmitted. It is an important aspect of storage security and reliability which are prerequisite for most computer system applications. This paper proposes a new technique for improving the detection of data integrity violations. The method is set up the check determinant approach. Each block of data is arranged in a matrix form, and then into its corresponding oblique matrix. Because of the new arrangement in the block elements through the oblique matrix, a powerful error detection mechanism is obtained. Simulation results show that the new method outperforms the traditional techniques.